What has Covid‐19 meant for the tax landscape?. Issue 5 (4th June 2021) - Harwood, Mark
Abstract : Although the past year has been a tricky one for many, let's start with a big positive – there remains plenty of great tax‐saving opportunities for the veterinary profession as we move through the Covid‐19 pandemic. In this article, I give a flavour of some of the tax changes that have been announced so far in 2021, and what they mean for the profession going forward.